NerveCheck: An inexpensive quantitative sensory testing device for patients with diabetic neuropathy. (March 2016) - Ponirakis, G.; Odriozola, M.N.; Odriozola, S.; Petropoulos, I.N.; Azmi, S.; Fadavi, H.; Alam, U.; Asghar, O.; Marshall, A.; Miro, A.; Kheyami, A.; Al-Ahmar, A.; et al.
Highlights: Nervecheck is the first inexpensive (500), portable device to quantify sensory loss. It measures the vibration, cold, warm perception threshold and heat pain threshold. It provide a simple categorical output of the severity of neuropathy. It has good reproducibility. Its diagnostic accuracy for neuropathy is comparable to established QST devices. Abstract: Aims: Sensory neuropathy is central to the development of painful neuropathy, and foot ulceration in patients with diabetes. Currently, available QST devices take considerable time to perform and are expensive. NerveCheck is the first inexpensive (500), portable QST device to perform both vibration and thermal testing and hence evaluate diabetic peripheral neuropathy (DPN). This study was undertaken to establish the reproducibility and diagnostic validity of NerveCheck for detecting neuropathy. Methods: 130 subjects (28 with DPN, 46 without DPN and 56 control subjects) underwent QST assessment with NerveCheck; vibration perception and thermal testing. DPN was defined according to the Toronto criteria. Results: NerveCheck's intra correlation coefficient for vibration, cold and warm sensation testing was 0.79 (95% LOA: −4.20 to 6.60), 0.86 (95% LOA: −1.38 to 2.72) and 0.71 (95% LOA: −2.36 to 3.83), respectively. The diagnostic accuracy (AUC) for vibration, cold and warm sensation testing was 86% (SE: 0.038, 95% CI 0.79–0.94), 79% (SE: 0.058, 95% CI 0.68–0.91) and 72% (SE: 0.058, 95% CI 0.60–0.83), respectively. Conclusions: This study shows that NerveCheck has good reproducibility and comparable diagnostic accuracy to established QST equipment for the diagnosis of DPN.